Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I need to calculate the following indefinite integral:

$$I=\int \frac{1}{\cos^3(x)}dx$$

I know what the result is (from Mathematica):


but I don't know how to integrate it myself. I have been trying some substitutions to no avail.

Equivalently, I need to know how to compute:

$$I=\int \sqrt{1+z^2}dz$$

which follows after making the change of variables $z=\tan x$.

share|cite|improve this question
up vote 20 down vote accepted

We have an odd power of cosine. So there is a mechanical procedure for doing the integration. Multiply top and bottom by $\cos x$. The bottom is now $\cos^4 x$, which is $(1-\sin^2 x)^2$. So we want to find $$\int \frac{\cos x\,dx}{(1-\sin^2 x)^2}.$$ After the natural substitution $t=\sin x$, we arrive at $$\int \frac{dt}{(1-t^2)^2}.$$ So we want the integral of a rational function. Use the partial fractions machinery to find numbers $A$, $B$, $C$, $D$ such that $$\frac{1}{(1-t^2)^2}=\frac{A}{1-t}+\frac{B}{(1-t)^2}+ \frac{C}{1+t}+\frac{D}{(1+t)^2}$$ and integrate.

share|cite|improve this answer

Hint: rewrite the integral as

$$\int \sec ^3 (x) \, dx$$

Recall the identity $\sec^2(x)=\tan^2(x)+1$.

So, substituting, you get

$$\int\sec(x)(\tan^2(x)+1) \, dx=\int\tan(x)\tan(x)\sec(x) \, dx+\int\sec(x) \, dx.$$

The first integral can be solved by $u$-substitution and integration by parts, while the second, is an identity.

$$\int\tan(x) \, d\sec(x) = \tan(x)\sec(x)-\int\sec(x) \, d\tan(x)$$

But $\int\sec(x) \, d\tan(x)$ is the original integral. So write an equation and solve for $\int \sec^3(x)dx$

share|cite|improve this answer

With regards to your questions read this wikipedia page.

share|cite|improve this answer
cool.. a wikipedia page just for one integral – becko Jun 7 '12 at 2:22

$\newcommand{\+}{^{\dagger}}% \newcommand{\angles}[1]{\left\langle #1 \right\rangle}% \newcommand{\braces}[1]{\left\lbrace #1 \right\rbrace}% \newcommand{\bracks}[1]{\left\lbrack #1 \right\rbrack}% \newcommand{\ceil}[1]{\,\left\lceil #1 \right\rceil\,}% \newcommand{\dd}{{\rm d}}% \newcommand{\down}{\downarrow}% \newcommand{\ds}[1]{\displaystyle{#1}}% \newcommand{\equalby}[1]{{#1 \atop {= \atop \vphantom{\huge A}}}}% \newcommand{\expo}[1]{\,{\rm e}^{#1}\,}% \newcommand{\fermi}{\,{\rm f}}% \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,}% \newcommand{\half}{{1 \over 2}}% \newcommand{\ic}{{\rm i}}% \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow}% \newcommand{\isdiv}{\,\left.\right\vert\,}% \newcommand{\ket}[1]{\left\vert #1\right\rangle}% \newcommand{\ol}[1]{\overline{#1}}% \newcommand{\pars}[1]{\left( #1 \right)}% \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}}% \newcommand{\root}[2][]{\,\sqrt[#1]{\,#2\,}\,}% \newcommand{\sech}{\,{\rm sech}}% \newcommand{\sgn}{\,{\rm sgn}}% \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}}% \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert}$ \begin{align} &\color{#c00000}{\int\sec^{3}\pars{x}\,\dd x}= \int\sec\pars{x}\,\dd\tan\pars{x} = \tan\pars{x}\sec\pars{x} - \int\tan\pars{x}\bracks{\sec\pars{x}\tan\pars{x}}\,\dd x \\[3mm]&= \tan\pars{x}\sec\pars{x} - \int\sec^{3}\pars{x}\,\dd x +\int\sec\pars{x}\,\dd x \\[3mm]&= \tan\pars{x}\sec\pars{x} - \color{#c00000}{\int\sec^{3}\pars{x}\,\dd x} + \ln\pars{\sec\pars{x} + \tan\pars{x}} \end{align}

$$\color{#0000ff}{\large% \int\sec^{3}\pars{x}\,\dd x = \half\bracks{\tan\pars{x}\sec\pars{x} + \ln\pars{\vphantom{\LARGE A}\sec\pars{x} + \tan\pars{x}}}} $$

share|cite|improve this answer

It appears that Mathematica is using the "universal change" for trigonometric integrals $\tan(x/2)=t$:

share|cite|improve this answer

$\int \sqrt (1 + x^2) dx$

let $x = \tan \theta $

then $dx = \sec ^2\theta d\theta $

we have the integral is then: $\int \sec ^3\theta d\theta $

recall: $\tan ^2\theta + 1 = \sec ^2\theta $ and write as: $\int \sec \theta (\sec ^2\theta )d\theta $

continue with integration by parts, by letting:

$u = \sec \theta $


$dv = \sec ^2\theta d\theta $

we have:

$v = \tan \theta $


$du = \sec \theta \tan \theta d\theta $

and thus,

$uv - \int vdu$

is then:

$\sec \theta \tan \theta - \int \sec \theta \tan ^2\theta d\theta $


$\tan ^2\theta + 1 = \sec ^2\theta $

we have:

$\sec \theta \tan \theta - \int \sec \theta (\sec ^2\theta - 1) d\theta $

after distribution, altogether we have:

$\int \sec ^3\theta d\theta = \sec \theta \tan \theta - \int \sec ^3\theta d\theta - \int \sec \theta d\theta $

rearranging and collecting like-terms:

$2\int \sec ^3\theta d\theta = \sec \theta \tan \theta - \int \sec \theta d\theta $

$2\int \sec ^3\theta d\theta = \sec \theta \tan \theta - \ln |\sec \theta + \tan \theta |$

$\int \sec ^3\theta d\theta = (1/2)[\sec \theta \tan \theta - \ln |\sec \theta + \tan \theta |]$


without u\sin g integration tables, we can derive

$\int \sec \theta d\theta $


$=\int 1/\cos \theta d\theta $

$=\int \cos \theta /\cos ^2\theta d\theta $

$=\int \cos \theta /(1 - \sin ^2\theta ) d\theta $

let $u = \sin \theta $

then $du = \cos \theta d\theta $

we have: $\int 1/(1 - u^2) du$

partial fractions:

$A/(1 - u) + B/(1 + u) = 1$

$A + B = 1$

$A - B = 0$

$A = 1/2$

$B = 1/2$

we have:

$-(1/2)\ln |1 - u| + (1/2)\ln |1 + u|$

by rules of logarithms:

$(1/2)\ln |(1 + u)/(1 - u)|$

$(1/2)\ln |(1 - u^2)/(1 - u)^2|$

by rules of logarithms:

$\ln |\sqrt (1 - u^2)/(1 - u)|$


$u = \sin \theta $

$\ln |\sqrt (1 - \sin ^2\theta )/(1 - \sin \theta )|$

$\ln |\sqrt \cos ^2\theta /(1 - \sin \theta )|$

$\ln |\cos \theta /(1 - \sin \theta )|$

$\ln |\cos \theta (1 + \sin \theta )/(1 - \sin ^2\theta )|$

$\ln |\cos \theta (1 + \sin \theta )/\cos ^2\theta |$

$\ln |1/\cos \theta + \sin \theta /\cos \theta |$

$\ln |\sec \theta + \tan \theta |$


but the integral of $\int \sec ^3\theta d\theta $ is:

$\int \sec ^3\theta d\theta = (1/2)[\sec \theta \tan \theta - \ln |\sec \theta + \tan \theta |]$ + CONS\tan T

and \sin ce $\tan \theta = x = x/1 =$ opposite/adjacent, with the pythagorean theorem, we derive: hypotenuse = $\sqrt (1 + x^2)$ and thus, $\sec \theta $ = hypotenuse/adjacent = $\sqrt (1 + x^2)$

$\int \sqrt (1 + x^2) dx$ $= (1/2)[x\sqrt (1 + x^2) - \ln |\sqrt (1 + x^2) + x|]$ + CONS\tan T

share|cite|improve this answer

Immediate calculation of $$\int \sec ^{3}xdx.$$

We need the basic formulas of the first two derivatives of $\sec x:$\begin{eqnarray*} (\sec x)^{\prime } &=&\sec x\tan x \\ (\sec x)^{\prime \prime } &=&2\sec ^{3}x-\sec x \end{eqnarray*} Then \begin{eqnarray*} \int \sec ^{3}xdx &=&\frac{1}{2}\int \sec xdx+\frac{1}{2}\int (\sec x)^{\prime \prime }dx \\ &=&\frac{1}{2}\ln \left\vert \sec x+\tan x\right\vert +\frac{1}{2}(\sec x)^{\prime }+C \\ &=&\frac{1}{2}\ln \left\vert \sec x+\tan x\right\vert +\frac{1}{2}\sec x\tan x+C. \end{eqnarray*}

share|cite|improve this answer

Let $I = \int \sec^3 x dx$

$$\begin{align} I &= \int \sec^3 \;\; \text{(by parts)} \\ &= \int \sec^2 x \sec x dx \\ &= \tan x \sec x - \int \tan x (\sec \tan x) dx \\ &= \tan x \sec x - \int \sec x (\sec^2 x - 1) dx\\ &= \tan x \sec x - I \int \sec x dx \;\; \text{( No need for "c" yet; still an integral to go)} \end{align}$$


$$2I = \sec x \tan x + \int \sec x dx$$ so

$$ I - (1/2) \sec x \tan x + \ln (A (\sec x + tan x)) $$ (here, $c = ln|A|$)

For int sqrt (1 + z^2) dz put z = sinh u and obtain an equivalent result

share|cite|improve this answer

For the integral: $$\int \sqrt{1+x^2}dx$$ Put $x=\sinh(u), dx=\cosh(u)du$ The integral becomes: $$\int (\cosh(u))^2 du$$ Use the definition $$\cosh(u)=\frac{e^u+e^{-u}}{2}$$ to see the integral becomes: $$\int \frac{e^{2u}+2+e^{-2u}}{4}du$$ So remembering $$\int e^{au}du=\frac{e^{au}}{a}$$ The integral evaluates to: $$\frac{e^{2u}}{8}+\frac{e^{-2u}}{-8}+\frac{u}{2}+C=\frac{\sinh(2u)}{4} +\frac{u}{2}+ C=\frac{\sinh(u)\cosh(u)}{2} +\frac{u}{2}+ C $$ Putting every thing in terms of x, the integral is $$\frac{x\sqrt{x^2+1}}{2}+\frac{\sinh^{-1}(x)}{2}+C$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.